Environmental problems of timber rafting - Vinogradov, Alexey Yu.; Obyazov, Viktor A.; Lazareva Tatiana А. (Journal of the Belarusian State University. Ecology, 2020)
The paper considers the main points of both the positive and negative impact of the molten alloy on the ecological state of rivers and watersheds are estimated. Concrete measures are proposed to reduce the chemical effects and mechanical pollution of water bodies. Arguments about the need for channel reclamation are presented and a concrete plan for land reclamation is proposed with the aim of improving the recreational capabilities of small rivers, purifying water, improving the state of the forest fund by reducing flooding of the territory.